Genes and pathways revealed by whole transcriptome analysis of milk derived bovine mammary epithelial cells after Escherichia coli challenge - Iso-Touru, Terhi (BioMed Central, 2025)
Mastitis, inflammation of the mammary gland, is the costliest disease in dairy cattle and a major animal welfare concern. Mastitis is usually caused by bacteria, of which staphylococci, streptococci and Escherichia coli are most frequently isolated from bovine mastitis. Bacteria activate the mammary immune system in variable ways, thereby influencing the severity of the disease. Escherichia coli is a common cause of mastitis in cattle causing both subclinical and clinical mastitis. Understanding of the molecular mechanisms that activate and regulate the host response would be central to effective prevention of mastitis and breeding of cows more resistant to mastitis. We used primary bovine mammary epithelial cell cultures extracted noninvasively from bovine milk samples to monitor the cellular responses to Escherichia coli challenge. Differences in gene expression between control and challenged cells were studied by total RNA-sequencing at two time points post-challenge. In total, 150 and 440 (Padj < 0.05) differentially expressed genes were identified at 3 h and 24 h post-challenge, respectively. The differentially expressed genes were mostly upregulated at 3 h (141/150) and 24 h (424/440) post-challenge. Our results are in line with known effects of E. coli infection, with a strong early inflammatory response mediated by pathogen receptor families. Among the most significantly enriched early KEGG pathways were the TNF signalling pathway, the cytokine-cytokine receptor interaction, and the NF-kappa B signalling pathway. At 24 h post-challenge, most significantly enriched were the Influenza A, the NOD-like receptor signalling, and the IL-17 signaling pathway.